Languages in contact : French, German and Romansch in twentieth-century Switzerland - Weinreich, Uriel (John Benjamins Pub. Co., 2011)
"The appearance of Uriel Weinreich's Languages in Contact: Findings and Problems (1953) marked a milestone in the study of multilingualism and language contact. Yet until now, few linguists have been aware that its main themes were first laid out in Weinreich's Columbia University doctoral dissertation of 1951, Research Problems in Bilingualism with Special Reference to Switzerland. Based on the author's fieldwork, it contains a detailed report on language contact in Switzerland in the first half of the 20th century, especially along the French-German linguistic border and between German and Romansh in the canton of Grisons (Graubünden). The present edition reproduces Weinreich's original text in full, with only minor alterations and corrections, as well as the author's fieldwork photographs and many of his hand-drawn diagrams. A new foreword reviews Weinreich's life and legacy, as well as developments in contact linguistics and the Swiss linguistic situation over the past 60 years. With selected comments on noteworthy points and references to more recent literature, this volume will be of interest not only to those working on the languages of Switzerland, or specialists in language contact, but all scholars today whose work builds on the broad and lasting foundations laid over half a century ago by Uriel Weinreich."--